School Culture Management in Efforts to Improve the Quality of Primary School Education In Jember - Rizal, Syaiful (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
In facing various challenges and competition in schools, it is necessary to involve all components/school members in order to build relationships or partnerships with other institutions in improving the quality of education in the school. Efforts to increase and improve the quality of elementary school education need to be done through an effective school culture. Because improving the quality of elementary school education cannot be separated from the basis of school culture. With this cultural base, school principals, teachers, students and parents will feel a sense of belonging, so they will maintain, improve and strive to improve the quality of school education. The aim of this paper is to develop a model for improving the quality of elementary school education based on school culture to create effective schools. The results of the researchers' findings show that the model that can be used in basic education to improve the quality of basic education based on school culture is the reform model. Efforts to improve the quality of basic education can be carried out through various school reforms related to various dimensions, such as the principal dimension, the teacher dimension, the student dimension, the student parent dimension, and the stakeholder dimension. Efforts to improve and increase the quality of a school are seen from the aspect of honesty. Apart from honesty, other core values ​​that can be instilled in basic education students are discipline, responsibility, patience, humility and tolerance.